Online Public Attention Toward Premature Ejaculation in Mainland China: Infodemiology Study Using the Baidu Index - Shanzun Wei; Ming Ma; Xi Wen; Changjing Wu; Guonian Zhu; Xiangfu Zhou (JMIR Publications, 2021)
BackgroundPremature ejaculation (PE) is one of the most described psychosocial stress and sexual complaints worldwide. Previous investigations have focused predominantly on the prospective identification of cases that meet researchers' specific criteria. The genuine demand from patients with regard to information on PE and related issues may thus be neglected. ObjectiveThis study aims to examine the online search trend and user demand related to PE on a national and regional scale using the dominant major search engine in mainland China. MethodsThe Baidu Index was queried using the PE-related terms for the period of January 2011 to December 2020. The search volume for each term was recorded to analyze the search trend and demographic distributions. For user interest, the demand and trend data were collected and analyzed. ResultsOf the 36 available PE search keywords, 4 PE searching topics were identified. The Baidu Search Index for each PE topic varied from 46.30% (86,840,487/187,558,154) to 6.40% (12,009,307/187,558,154). The annual percent change (APC) for the complaint topic was 48.80% (P<.001) for 2011 to 2014 and -16.82% (P<.001) for 2014 to 2020. The APC for the inquiry topic was 16.21% (P=.41) for 2011 to 2014 and -11.00% (P<.001) for 2014 to 2020. For the prognosis topic, the annual APC was 11.18% (P<.001) for 2011 to 2017 and -19.86% (P<.001) for 2017 to 2020. For the treatment topic, the annual APC was 14.04% (P<.001) for 2011 to 2016 and -38.83% (P<.001) for 2016 to 2020. The age distribution of those searching for topics related to PE showed that the population aged 20 to 40 years comprised nearly 70% of the total search inquiries (second was 17.95% in the age group younger than 19 years). People from East China made over 50% of the total search queries. ConclusionsThe fluctuating online popularity of PE searches reflects the real-time population demands. It may help medical professionals better understand population interest, population concerns, regional variations, and gender differences on a nationwide scale and make disease-specific health care policies. The internet search data could be more reliable when the insufficient and lagging registry data are completed.